Class Management of Learning Models Design in Elementary School: Research Results Metasynthesis - Nurchasanah, Nurchasanah; Suyono, Suyono; Murthado, Nurul; Habsari, Zakia (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
One of teacher obligations is managing the class which is maintaining the optimal learning conditions. The class management of the design of the elementary school literacy learning model from research results needs to be examined in hope that it can be taken into consideration for managing classes in schools. With that consideration, the purpose of this study is to describe the results of the metasynthesis of classroom management research design of the elementary literacy learning model in terms of (1) the beginning, (2) the core, and (3) the end of learning. The design used is qualitative with metasynthesis research. The research data is in the form of verbal classroom management data at the beginning, core, and end of the design of elementary literacy learning models that is taken from student research documentations of the results of class development and action. Data is taken by documentation techniques and analyzed based on data analysis guidelines through the following procedures: reading research results, identifying data, reducing data, analyzingsynthesizing, validating analysis results, concluding, and interpreting results. The results showed that the classroom management of elementary literacy learning model design was seen at each stage of learning with varying classroom management